Women, Work, and Revolution: A Do-It-Yourself Practice. (2nd January 2016) - Reed, Sara Desvernine
Abstract: Through a study of images of women engaged in work both in and outside the home found in the Cuban magazine Mujeres during its initial decade of production, this article examines the magazine's representations of labor as a means of fostering collective participation and loyalty to the new regime in post-revolutionary Cuba. Mujeres aimed to propagate images of women participating in revolutionary life to engender collective support for the Fidel Castro regime, which simultaneously reinforced and subverted existing gender stereotypes and, in the process, defined the new Cuban woman. In fact, the editors of Mujeres encouraged a do-it-yourself approach to household maintenance and care that prompted readers to embrace self-directed, creative design strategies as a component of their revolutionary activism.